2022
DOI: 10.2147/cmar.s347852
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Correlated with the Development of Immune-Related Adverse Events in Patients with Non-Small Cell Lung Cancer Treated with Immune Checkpoint Inhibitors

Abstract: Similar to the neutrophil-to-lymphocyte ratio and lung immune prognostic index (LIPI), immune-related adverse events (irAEs) were favorable prognostic factors in several studies, for patients with non-small cell lung cancer who received immune checkpoint inhibitors (ICIs). However, few studies have investigated patient characteristics and markers that predict the development of irAEs, and factors predicting the development of irAEs have not been clarified. Thus, the present study aimed to examine the predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%. This reflects heterogeneity including in study setting (observational vs randomized clinical trial), patient characteristics (cancer stage, PD-L1 status, geographical location, race and ethnicity), treatment parameters (ICI agent used either alone or combined with chemotherapy, treatment line), and irAE grading . In our cohort, the incidence of clinically meaningful irAEs was 37.0%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The incidence of reported irAEs in NSCLC varies widely, ranging from 24.0% to 70.5%. This reflects heterogeneity including in study setting (observational vs randomized clinical trial), patient characteristics (cancer stage, PD-L1 status, geographical location, race and ethnicity), treatment parameters (ICI agent used either alone or combined with chemotherapy, treatment line), and irAE grading . In our cohort, the incidence of clinically meaningful irAEs was 37.0%.…”
Section: Discussionmentioning
confidence: 96%
“…Why irAEs occur in some patients but not others remains poorly understood, but a variety of predictive factors in NSCLC have been described. Demographic characteristics (age, sex, race, body mass index, and ECOG), concomitant medications (corticosteroids, proton pump inhibitors, and antibiotics), peripheral laboratory markers (hemoglobin, albumin, C-reactive protein, and others), tumor characteristics (histology, stage, PD-L1 expression, driver mutation status, and disease burden), and treatment-related factors (treatment line, response, ICI agent, concurrent chemotherapy, time to starting ICI, cumulative dose, and cumulative cycles of ICI) are inconsistently reported as predictive factors associated with irAE development . In our cohort, we identified several baseline patient characteristics associated with irAE development: 60 years or older, ECOG performance status 0, high expression of PD-L1, absence of bone metastases, DNLR of 3 or less, and levels of hemoglobin, albumin, and LDH within reference range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several predictive risk factors were associated with ICIinduced ir-AEs in the treatment of advanced NSCLC. According to previous reports, first-line treatment with ICIs and lung immune prognostic index (LIPI) were independent predictive risk factors for ir-AEs in patients with advanced NSCLC (14). Furthermore, concomitant chemotherapy use, high body mass index (BMI), and presence of epidermal growth factor receptor (EGFR) mutation were significant predictors for ir-AEs (15).…”
Section: Discussionmentioning
confidence: 97%
“…Negative relationships between disease course and the musculoskeletal, respiratory and nonspeci c symptom clusters was found in our study, with a shorter disease course associated with a higher symptom burden. It has been reported that patients treated with rst-line ICI therapies are more likely to develop irAEs but have better clinical outcomes [24]. Patients with a short disease course are mostly treated with rst-line ICI therapies or combined therapies, which may induce a better immune response but also the development irAEs, leading to various symptoms.…”
Section: Factors Associated With Symptom Clustersmentioning
confidence: 99%